A hierarchical integrated chassis control strategy based on wheel force feedback. Issue 4 (2016) - Li, Shiqian; Arat, Mustafa Ali
The motivation to investigate a novel integrated chassis control (ICC) strategy emerges from recent advances in on-board force transducers. This study proposes a novel hierarchical framework adopting feedback control on tyre force level, and an on-target high level control algorithm including Force Reference Generator and allocation strategy to supervise front steering and braking subsystems. In the proposed method, force reference is generated regarding linear vehicle behaviour and guaranteed to be achievable, bounded by tyre grip limit. Allocation strategy tracks force reference and penalises undesired vehicle body motion, capturing significantly faster dynamics. In order to address the non-linearities and uncertainties of the vehicle model, a modified model reference adaptive control (MRAC) scheme is used, which both stabilises the lateral dynamics and maintains maximum lateral performance. The proposed method is validated and evaluated on a multi-body vehicle model simulation.